Time and quality of admissions: nursing workload - Simone Aparecida Trovó; Danielle Fabiana Cucolo; Marcia Galan Perroca (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to measure the average time spent by the nursing staff during patient admission and investigate their compliance with the activities described by the Nursing Interventions Classification; evaluate the degree of interference in the workload of the team. Methods: observational with time measurement through software. We followed 199 admissions made by the nursing staff in seven units, using two validated instruments. Total scores ≥ 70% and 50% validated the process. Results: the average time of nurses ranged from 5.5 (standard deviation = 2.3) to 13 (standard deviation = 1.1) minutes; and the auxiliary / technician, between 4.7 (standard deviation = 2.1) and 6.8 (standard deviation = 2.0) minutes (p ≤ 0.01). We qualified six admissions made by nurses and 33 by assistants/technicians. The intervention spent 16.3% to 31.5% of the working hours of the team. Conclusions: admission impacts nursing workload and needs to be considered both in the measurement of activities and in the sizing of the nursing staff.